ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CV. HELDA TRAVEL BERSAUDARA SANGATTA - Triska Aprilo; Riduansah; Endang Prihatiningsih (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
This study aims to analyze the effect of service quality on customer satisfaction at CV. Helda Travel Sangatta Brothers. This study uses five independent variables. The data in this study were collected through the distribution of questionnaires and observation. The sampling technique used is purposive sampling. The data analysis method used is quantitative analysis, namely validity, reliability, classical assumption test, multiple linear regression analysis, t test, coefficient of determination and f test. Based on data analysis, the results of the study indicate that the indicators in this study are valid and reliable. While reliability has a negative effect and does not significantly affect customer satisfaction.